P52a - T. Tyrinova; A. Ostanin; S. Mishinov; L. Sakhno; S. Chernov; V. Stupak; E. Chernykh (EJC Supplements, 2015)
Glioma is the most common type of primary brain tumor. Despite aggressive therapy, glioma virtually always recurs. Soluble factors produced by glioma cells play an important role in progression of tumor growth. Glioma-derived soluble factors can stimulate tumor cell proliferation in autocrine and paracrine manners, affect the tumor microenvironment and promote angiogenesis and metastasis. Besides, glioma-derived cytokines are able to disturb antitumor immune response by inhibiting the functions of effector lymphocytes and inducing immunosuppressive cells. The aim of the present study was to determine the profile of cytokines produced by primary low-grade and high-grade glioma cell cultures. The study was held in 21 patients with brain tumors after receiving a written informed consent. There were 6 patients with histologically verified low-grade glioma (Grade II) and 15 patients – with high-grade glioma (Grade III–IV). Tumor tissues from patients were obtained during surgical resection. Cell suspensions were prepared by mechanical and enzymatic disaggregation followed by culturing in DMEM/F12 medium containing 10% FCS. The levels of 27 cytokines were measured using multiplex analysis (Bio-Rad, USA) in 7-days supernatants collected upon reaching the cellular subconfluence. Low-grade glioma cells produced low level (Me <25 pg/ml) of pro-inflammatory cytokines IL-1β, TNFα and anti-inflammatory cytokines IL1-ra, IL-10, IL-13. The level of these cytokines in supernatants of high-grade glioma cultures were in the middle range (25–500 pg/ml), excepting IL-1β (Me 5.9 pg/ml). Concerning cytokines with immunoregulatory activity in supernatants of low-grade glioma cultures, only IL-12 level was in the middle range (Me 77 pg/ml), whereas the level of other immunoregulatory cytokines (IL-2, IFNγ, IL-4, IL-5, IL-15, IL-17) was low (Me <25 pg/ml). High-grade glioma cells actively produced not only IL-12 (Me 336 pg/ml), but also IFNγ and IL-15 (Me 355 pg/ml and Me 57 pg/ml, respectively). The level of growth factors and cytokines, which act as regulators of hemo- and immunopoesis, was low in supernatants of low-grade glioma cultures. Median concentration of G-CSF, GM-CSF, IL-7, FGFb and PDGF was less than 25 pg/ml, but IL-9 concentration was in the middle range (Me 74 pg/ml) . High-grade glioma cultures produced, besides IL-9, also G-GSF (Me 263 pg/ml), FGFb (Me 60 pg/ml) and PDGF (Me 63 pg/ml). The level of FGFb and G-GSF correlated with the glioma grade (R = 0.87, p = 0.002, and R = 0.66, p = 0.002, respectively). The IL-7 and GM-CSF level in high-grade culture supernatant was low (Me <25 pg/ml). IL-6 and VEGF play important role in the maintenance of tumor cell proliferation and the stimulation of tumor angiogenesis. Both low-grade and high-grade glioma cultures produced high level (>500 pg/ml) of IL-6 (Me 1933 pg/ml and 3531 pg/ml, respectively) and VEGF (Me 1004 pg/ml and 14887 pg/ml, respectively). VEGF level correlated with glioma grade (R = 0.86, p = 0.002). Concerning CC-chemokines the level of Eotaxin was low in low-grade glioma cultures (Me 11 pg/ml). The mild-level production was found for MIP-1α (Me 71 pg/ml) and RANTES (231 pg/ml), high-level – for MCP-1 (Me 9468 pg/ml) and MIP-1β (Me 990 pg/ml). High-grade glioma cells produced not only MIP-1α (Me 208 pg/ml) and RANTES (Me 311 pg/ml) in the middle range but also Eotaxin (Me 107 pg/ml). Eotaxin level correlated with the glioma grade (R = 0.87, p = 0.002). High-grade glioma cells produced highlevel of MCP-1 (Me 9868 pg/ml) and MIP-1β (Me 1923 pg/ml). Both low-grade and high-grade glioma cells produced high level of CXC-chemokines IL-8 and IP-10 (Me >1000 pg/ml). The level of IL-8, which acts as chemoattractant for immune cells as well as for endothelial cells involved in angiogenesis, correlated with glioma grades (R = 0.72, p = 0.002). Thus, the grade of gliomas associated with broadening the spectrum of cytokines and enhanced level of cytokines production by tumor cells.